2017
DOI: 10.1016/j.foodchem.2017.05.092
|View full text |Cite
|
Sign up to set email alerts
|

Successive harvesting affects yield, chemical composition and antioxidant activity of Cichorium spinosum L.

Abstract: a b s t r a c tIn the present study, the effect of successive harvesting on yield, chemical composition and antioxidant activity of Cichorium spinosum plants was examined. C. spinosum plants were grown from seeds sown in seed trays containing peat and young seedlings were transplanted in 2L pots containing peat and perlite (1:1 v/v). Plants were harvested two or three times during two consecutive growing periods. Total fresh weight and number of leaves were higher for successive harvests in both growing period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
41
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 35 publications
16
41
2
Order By: Relevance
“…In addition, total fresh weight was higher when plants were harvested twice comparing to plants that were harvested only once for all the fertilizer treatments, whereas fresh weight for second harvest was significantly lower than that of the first harvest. Similar results have been reported by the authors (Petropoulos et al, 2017b) who evaluated the effect of successive harvesting on yield and chemical composition of C. spinosum leaves. Higher contents of ammonium nitrogen in the nutrient solution (treatments F4 and F5) had no beneficial effect in terms of fresh weight during the 2nd growing period, probably due to higher growth rates of plants during this period and the shorter growth cycles due to early anthesis, comparing to the 1st growing condition.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In addition, total fresh weight was higher when plants were harvested twice comparing to plants that were harvested only once for all the fertilizer treatments, whereas fresh weight for second harvest was significantly lower than that of the first harvest. Similar results have been reported by the authors (Petropoulos et al, 2017b) who evaluated the effect of successive harvesting on yield and chemical composition of C. spinosum leaves. Higher contents of ammonium nitrogen in the nutrient solution (treatments F4 and F5) had no beneficial effect in terms of fresh weight during the 2nd growing period, probably due to higher growth rates of plants during this period and the shorter growth cycles due to early anthesis, comparing to the 1st growing condition.…”
Section: Resultssupporting
confidence: 90%
“…Luna et al (2013) and Sofo et al (2016) have also suggested that antioxidant properties of lettuce may be affected by fertilization treatments and growing systems, while Fallovo et al (2011) have suggested that apart from nutrient solution composition, growing season may also affect chemical composition of lettuce. The detected phenolic compounds in C. spinosum leaves and have been previously reported by the authors (Petropoulos et al, 2017a(Petropoulos et al, , 2017b(Petropoulos et al, , 2017c. The same compounds have been identified in other cultivated Cichorium species (Carazzone et al, 2013;Ferioli et al, 2015).…”
Section: Tablesupporting
confidence: 81%
See 1 more Smart Citation
“…Palmitic acid (C16:0) and palmitoleic acid (C16:1) constituted, on average, 74.8% and 75% of the SFA and MUFA, respectively; oleic acid (C18:1 n 9c) was the second most abundant (22.7% on average) MUFA, whereas α ‐linolenic acid (C18:3 n 3) constituted the primary (80.8%) PUFA and fatty acid in general, followed by linoleic acid (C18:2 n 6c), which represented 18.8% of the PUFA. Overall, the observed fatty acid composition was similar to the fatty acid profile reported for different ecotypes of C. spinosum and C. spinosum harvested at different times . Although a lower omega‐6/omega‐3 fatty acids ratio was observed in the present study compared to that reported by Petropoulos et al .…”
Section: Resultssupporting
confidence: 89%
“…In addition, successive harvesting has also been one of the factors that affects chemical properties and dry matter yield of medicinal plants. Frequent harvesting has been reported to affect the phytochemical contents and antioxidant activities of Stevia rebaudiana Bertoni (Tavarini et al, 2015) and Chicorium spinosum L. (Petropoulos et al, 2017). Successive harvesting at 35-day and 30-day interval has been found to decrease the dry matter yield of Moringa oleifera Lam (Amaglo et al, 2007) and Talinum triangulare (Jacq.)…”
Section: Introductionmentioning
confidence: 99%